Studi Fenomenologi Penggunaan Aplikasi Sistem Informasi Manajemen Rumah Sakit dalam Meningkatkan Efektivitas dan Efisiensi Pelayanan di RS Universitas Tanjungpura - Yudi Pamungkas, Rofi; Sampurno, Edi; Nurunniyah, Siti (SPT. haria Journal and Education Center Publishing, 2026)
Background: Implementation of Hospital Management Information Systems (HMIS/SIMRS) is a strategic effort to improve healthcare effectiveness and efficiency. However, the process still faces challenges including user resistance, infrastructure limitations, and human resource readiness. Objective: To comprehensively explore the perceptions, experiences, and barriers faced by Professional Care Providers (PPA) in using SIMRS (SIMGOS V2) at RS Universitas Tanjungpura, Pontianak. Methods: Qualitative research using hermeneutic phenomenology involving 9 PPAs selected via purposive sampling. Data were collected through in-depth interviews, three Focus Group Discussion (FGD) sessions, participatory observation, and document analysis. Data analysis followed the hermeneutic circle principle exploring lived experiences across four phenomenological dimensions: temporal, spatial, embodied, and relational. Validity was ensured through triangulation, member checking, and peer debriefing. Results: A paradoxical phenomenon was identified: SIMGOS V2 significantly improved operational efficiency (accelerated workflows, resource savings, reduced administrative burden) but has not fully achieved clinical effectiveness due to incomplete system integration. Fundamental transformation occurred across four dimensions: temporal (time efficiency with new systemic pressures), spatial (space virtualization with digital access gaps), embodied (literacy transformation from manual-tactile to digital-visual), and relational (information democratization with fragmentation of interpersonal warmth). Main barriers include imperfect system integration, unstable network infrastructure, and resistance as negotiation of professional identity. Conclusion: SIMRS implementation represents a fundamental socio-technical transformation requiring a holistic approach sensitive to its meaning for users. Hermeneutic phenomenology successfully uncovered hidden meaning layers in SIMRS technical evaluation.